2017
DOI: 10.1001/jamadermatol.2017.1877
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ibrutinib Treatment With Bleeding Complications in Cutaneous Surgery

Abstract: 4. Herrmann T, Günther C, Csere P. Localized morphea-a rare but significant secondary complication following breast cancer radiotherapy: case report and review of the literature on radiation reaction among patients with scleroderma/morphea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Shatzel et al recommend against taking fish oil while on ibrutinib [9]. described two patients on ibrutinib therapy who had post-operative bleeding complications after Mohs surgery to remove facial SCC [11]. The platelet counts were in the normal range for both patients at the time of surgery.…”
Section: Case Discussionmentioning
confidence: 99%
“…Shatzel et al recommend against taking fish oil while on ibrutinib [9]. described two patients on ibrutinib therapy who had post-operative bleeding complications after Mohs surgery to remove facial SCC [11]. The platelet counts were in the normal range for both patients at the time of surgery.…”
Section: Case Discussionmentioning
confidence: 99%
“…Resolution of complications was reported by day 10 in both cases. Given the increased bleeding risk associated with ibrutinib in a patient population with a greater bleeding risk at baseline, it is suggested that dermatologists and dermatologic surgeons work closely with hematologists to consider withholding ibrutinib treatment prior to surgical procedures 78 …”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Given the increased bleeding risk associated with ibrutinib in a patient population with a greater bleeding risk at baseline, it is suggested that dermatologists and dermatologic surgeons work closely with hematologists to consider withholding ibrutinib treatment prior to surgical procedures. 78 Idelalisib Idelalisib inhibits the delta-isoform of phosphatidylinositol-3 kinases (PI3K), a critical signal transduction pathway restricted to the hematopoietic lineage. 30 It is FDA approved for combination therapy with rituximab in relapsed CLL.…”
Section: Bleedingmentioning
confidence: 99%
“…Although ibrutinib is not usually considered on presurgical proformas, its bleeding risk exceeds that of oral anticoagulants, and complications have been reported. 4,7 A practical consideration from our case is that treatment discontinuation 3-7 days before and after surgery should be considered in liaison with Haematology colleagues. 4,7…”
mentioning
confidence: 99%
“…4,7 A practical consideration from our case is that treatment discontinuation 3-7 days before and after surgery should be considered in liaison with Haematology colleagues. 4,7…”
mentioning
confidence: 99%